Initial studies on squalene from some marine microalgae isolated in Vietnam - Ngoc Mai, Dinh Thi; Ha, Nguyen Cam; Thom, Le Thi; Hong, Dang Diem (Academia Journal of Biology, 2013)
Squalene is a highly unsaturated aliphatic hydrocarbon and belongs to the triterpene group of oils. Squalene is the last metabolite preceding sterol ring formation in the biosynthetic cholesterol pathway. It is normally used in its natural form as a moisturizing or emollient agent in pharmaceuticals and cosmetic preparations. More importantly, it is a potential oxidation inhibitor; it can protect cell against free radicals, strengthen the body’s immune system and decrease the risk for various cancers. In this study, we presented the results of initial research on squalene from seven marine microalgal species isolated in Vietnam coasts. Based on colorimetric method, squalene content in these microalgae was determined. Schizochytrium mangrovei reached the highest squalene content of 122 mg/g. Squalene content of 21.090 mg/g for Thraustochytrium mangrovei, 6.300 mg/g for Dunaliella tetiolecta, 9.700 mg/g for Isochrysis galbana, 0.193 mg/g Nannochloropsis oculata, 1.850 mg/g for Tetraselmis convolutae and 3.300 mg/g for Chlorella vulgaris were obtained. Moreover, thin layer chromatography and high performance liquid chromatography methods were successfully applied to the determination of squalene in S. mangrovei. The squalene content of S. mangrovei analysed by TLC and HPLC reached 12.630 mg/g of nonsaponifiable lipid, 0,405 mg/g of total lipid and 0,203 mg/g of dry biomass.